2018
DOI: 10.2131/jts.43.19
|View full text |Cite
|
Sign up to set email alerts
|

Effect of gestational cadmium exposure on fetal growth, polyubiquitinated protein and monoubiqutin levels in the fetal liver of mice

Abstract: -Cadmium (Cd) is an environmental pollutant present in contaminated water, food and soil. Cd adversely affects fetal development. We exposed pregnant mice to daily oral doses of 5 and 10 mg/kg Cd and examined fetal growth. It was demonstrated that the exposure to Cd (10 mg/kg) during gestation caused fetal growth retardation (FGR). Investigation of the ubiquitin-proteasome system in fetal livers of mice exposed to gestational Cd revealed increased polyubiquitinated protein accumulation, contrasting with decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Recently, the expression of several novel genes has been suggested to change in Cd renal toxicity. [48][49][50] Moreover, gestational exposure to Cd may affect fetal growth. 51,52) Furthermore, metabolomic analysis indicated that several amino acid derivatives in mouse urine may be useful indicators of renal damage caused by long-term Cd exposure.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, the expression of several novel genes has been suggested to change in Cd renal toxicity. [48][49][50] Moreover, gestational exposure to Cd may affect fetal growth. 51,52) Furthermore, metabolomic analysis indicated that several amino acid derivatives in mouse urine may be useful indicators of renal damage caused by long-term Cd exposure.…”
Section: Resultsmentioning
confidence: 99%